Answer:
<h2>
<em>2</em><em>2</em></h2>
<em>Option </em><em>C</em><em> </em><em>is</em><em> </em><em>the</em><em> </em><em>correct</em><em> </em><em>option</em><em>.</em>
<em>Solu</em><em>tion</em><em>,</em>
<em>
</em>
<em>(</em><em>opposite</em><em> </em><em>angles</em><em> </em><em>of</em><em> </em><em>parallelog</em><em>ram</em><em> </em><em>are</em><em> </em><em>equal </em><em>)</em>
<em>
</em>
<em>hope</em><em> </em><em>this</em><em> </em><em>helps</em><em>.</em><em>.</em><em>.</em>
<em>Good</em><em> </em><em>luck</em><em> on</em><em> </em><em>y</em><em>our</em><em> assignment</em><em>.</em><em>.</em>
Answer:
0.5, 0.25, 0.125
Step-by-step explanation:
the numbers half every time
Hello :
all n in N ; n(n+1)(n+2) = 3a a in N or : <span>≡ 0 (mod 3)
1 ) n </span><span>≡ 0 ( mod 3)...(1)
n+1 </span>≡ 1 ( mod 3)...(2)
n+2 ≡ 2 ( mod 3)...(3)
by (1), (2), (3) : n(n+1)(n+2) ≡ 0×1×2 ( mod 3) : ≡ 0 (mod 3)
2) n ≡ 1 ( mod 3)...(1)
n+1 ≡ 2 ( mod 3)...(2)
n+2 ≡ 3 ( mod 3)...(3)
by (1), (2), (3) : n(n+1)(n+2) ≡ 1×2 × 3 ( mod 3) : ≡ 0 (mod 3) , 6≡ 0 (mod)
3) n ≡ 2 ( mod 3)...(1)
n+1 ≡ 3 ( mod 3)...(2)
n+2 ≡ 4 ( mod 3)...(3)
by (1), (2), (3) : n(n+1)(n+2) ≡ 2×3 × 4 ( mod 3) : ≡ 0 (mod 3) , 24≡ 0 (mod3)
Answer:
A
Step-by-step explanation:
To evaluate f(- 3) substitute x = - 3 into f(x), that is
f(- 3) = 4(- 3) + 7 = - 12 + 7 = - 5 → A